Managing the Distribution of Employee Workload of the Hospital Staff - SRAVANI, A. (IJRDO - Journal of Business Management, 2018)
Attracting, recruiting, motivating and retaining the workforce is the main course of action for any organisations and also the success of any organization is highly dependent on how they maintain these practices. All this happens when the organisation will be providing fruitful Compensation Packages and the most important is the way the workload is distributed. Distribution of workload cannot be burdened or overburdened to any employee associated with the organisation. More over in today's world the organizations need to be more elastic so that they are set to build up their personnel to be fit for the present competition. Therefore, organizations are required to adopt a strategy to better manage the ‘Workload of the Employees’ to satisfy the both organizational objectives in developing and employee needs of satisfaction. In the total Work environment the term ‘employee workload’ refers to the managing of the workload management. Financially assisted programs are another way wherein organisation recognizes their responsibility to enlarge jobs and working conditions, including welfare programs that are admirable for the employees as well as for profitable growth of the organization. Employee workload program elements are such as – Recognition, Goodwill, Allowances, Perks, increments in the salary, Reward systems, a concern for employee job security and Job satisfying, career growth and employee participation in decision making process and so on.          An organization has been set up struggling in terms of managing the workers or the employee’s workload of their workforce. With the ever increasing burden of the workload the employees of the organisation becomes more vulnerable to stress and also burnouts which impacts the efficiency of the organization, totally.